THE MEANING AND FORM OF VERB TENSES IN ENGLISH AND UZBEK - Qosimova Munisa Feruz qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper investigates the intricate systems of verb tenses in English and Uzbek, exploring the similarities and differences in how these two languages express time and aspect. Through a comparative analysis, the study examines the morphological and syntactic  structures  employed  by  each  language  to  convey  temporal  and  aspectual information. Investigating the role of aspect in both languages, specifically focusing on how perfective, imperfective, and progressive aspects are expressed and how they interact  with  tense  to  create  a  more  comprehensive  understanding  of  temporal reference. Examining the morphological devices, such as affixes and auxiliaries, used by  each  language  to  convey  tense  and  aspect.  This  includes  a  comparison  of  the regularity and complexity of these morphological systems.